Post-harvest cleaning, sanitization, and microbial monitoring of soilless nutrient delivery systems for sustainable space crop production - Curry, Aaron B.; Spern, Cory J.; Khodadad, Christina L. M.; Hummerick, Mary E.; Spencer, LaShelle E.; Torres, Jacob; Finn, J. Riley; Gooden, Jennifer L.; Monje, Oscar (Frontiers in Plant Science, 2024)
Bioregenerative food systems that routinely produce fresh, safe-to-eat crops onboard spacecraft can supplement the nutrition and variety of shelf-stable spaceflight food systems for use during future manned exploration missions (i.e., Low Earth Orbit, Mars-transit, lunar and Martian habitats). However, current space crop production systems are not yet sustainable because they primarily utilize consumable granular media, and, to date, operate like single crop cycle, space biology experiments where root modules are sanitized prior to launch and discarded after each grow-out. Moreover, real-time detection of the cleanliness of crops produced in spacecraft is not possible. A significant paradigm shift is needed in the design of future space crop production systems as they transition from operating as single grow-out space biology experiments to becoming sustainable over multiple cropping cycles. Soilless nutrient delivery systems were used to demonstrate post-harvest sanitization and inflight microbial monitoring technologies to enable sequential cropping cycles in spacecraft. Post-harvest cleaning and sanitization prevent the buildup of biofilms and ensure a favorable environment for seedling establishment of the next crop. Inflight microbial monitoring of food and the watering system ensures food safety of spaceflight food systems. A sanitization protocol, heat sterilization at 60°C for 1 hour combined with soaking for 12 hrs in 1% hydrogen peroxide, developed in this study was compared against a standard hydroponic sanitization protocol during five consecutive crop cycles. Each cropping cycle included protocols for cultivation of a crop to maturity, followed by post-harvest cleaning and inflight microbial monitoring. Microbial sampling of nutrient solution reservoirs, root modules and plants demonstrated that the sanitization protocol can be used to grow safe-to-eat produce during multiple crop cycles. The cleanliness of reservoir and root module surfaces measured with aerobic plate counts was verified in near-real time by a qPCR-based inflight microbial monitoring protocol. Post-harvest sanitization and inflight microbial monitoring are expected to significantly transform the design of sustainable bioregenerative food and life support systems for future manned exploration missions beyond low earth orbit (LEO).